Development of a low cost micro fuel cell complete with power conversion - Lim, Vincent Ronggui. (2009)
The objective of the report was to design and fabricate a low cost micro fuel cell stack (μPEMFC). The author reviewed the components and technical considerations to take note in the design of the PEMFC which will affect the performance. Five main areas to tackle were the material selection, mechanical strength, electrical conductivity, sealing of the fuel cell and geometrical considerations.